2019
DOI: 10.1177/1534735419848494
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Hot Flashes in Cancer Patients: Clinical Characteristics and Traditional Chinese Medicine Diagnosis as Predictors of Treatment Response

Abstract: Background: Acupuncture is a recognized integrative modality for managing hot flashes. However, data regarding predictors for response to acupuncture in cancer patients experiencing hot flashes are limited. We explored associations between patient characteristics, including traditional Chinese medicine (TCM) diagnosis, and treatment response among cancer patients who received acupuncture for management of hot flashes. Methods: We reviewed acupuncture records of cancer outpatients with the primary reason for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…16 TCM diagnosis may be also important in predicting symptom response to acupuncture treatment. 17,18 Our previous review of acupuncture treatment for hot flashes among cancer patients observed that presence of damp accumulation in TCM diagnosis was correlated with greater hot flashes score reduction. 17 Future TCM acupuncture research should consider using TCM diagnosis to select a specific subgroup of a disease/syndrome or keep subgroups separate when deciding treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…16 TCM diagnosis may be also important in predicting symptom response to acupuncture treatment. 17,18 Our previous review of acupuncture treatment for hot flashes among cancer patients observed that presence of damp accumulation in TCM diagnosis was correlated with greater hot flashes score reduction. 17 Future TCM acupuncture research should consider using TCM diagnosis to select a specific subgroup of a disease/syndrome or keep subgroups separate when deciding treatment efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, particular features of TCM diagnoses were predictors of treatment response to acupuncture used for hot flashes in patients suffering from cancer. 43 Therefore, it may be logical to select patients for acupuncture based on an individualized process, in order to optimize the response obtained from treatment.…”
Section: Discussionmentioning
confidence: 99%
“…11 Research findings have mirrored this highly individualized acupuncture approach and indicate that TCM diagnosis may be predictive of acupuncture treatment response. 12,13 Few studies have actually compared using the fixed-point approach versus a more individualized approach that is used in clinical care. The appeal of using fixed points based on specific symptoms is that it is easy to replicate in the clinical research setting.…”
Section: Methodologic Differences Between Acupuncture Research and Clinical Practicementioning
confidence: 99%